The Impact of Service Quality, Product Quality and Content Marketing on Customer Satisfaction at Coffee Shop Tandalan Blitar - Basuki, Anas; Prasetyo, Edi Nur; Mashudi, Mashudi (Jurnal Pemasaran Kompetitif, 2024)
The expansion of business is currently becoming more difficult, and consequently, it is possible to classify the situation as an increasingly cutthroat competition between one coffee shop and another. Improving and paying attention to aspects like as service quality, product quality, and content marketing are some strategies that may be used in the coffee shop industry to increase customer satisfaction. The strategy that was taken in this study was quantitative, and the data was collected via the use of a questionnaire method that was provided to respondents. The sampling was done through the use of simple random sampling. The findings of the questionnaire were analysed, and several different tests, including the research instrument test, the normality test, the multiple linear regression test, and the hypothesis test, were carried out. It is possible to draw the following conclusions about coffee shop Tandalan's customer satisfaction based on the findings of the hypothesis testing: Service quality has a positive and significant effect on customer satisfaction at coffee shop Tandalan; Product quality has a positive and significant effect on customer satisfaction at coffee shop Tandalan; At coffee shop Tandalan, content marketing has a beneficial and noticeably large impact on the level of consumer happiness. At coffee shop Tandalan, the quality of service, the quality of products, and the quality of content marketing all have a concurrently positive and significantly impactful effect on customer satisfaction.